The Cambridge introduction to Tom Stoppard - Demastes, William W. (Cambridge introductions to literature, 2013)
"Tom Stoppard is widely considered to be one of the most important dramatists of contemporary theatre. In this Introduction, William Demastes provides an accessible overview of Stoppard's life and work, exploring all the complexity and variety that makes his drama so unique. Illustrated with images from a diverse range of Stoppard productions, the book provides clear evaluations of his major works, including Rosencrantz and Guildenstern are Dead, Travesties, Arcadia and The Coast of Utopia, to provide the most up-to-date assessment available. Detailed chapters situate each play in the context of its sources, which include Shakespeare and contemporary existential thought, espionage, quantum physics, chaos theory, romanticism, landscape design, nineteenth-century European intellectual thought and European totalitarianism. The book also includes a section on Stoppard's Academy Award-winning film Shakespeare in Love"--